Comparative techno-economic investigation of hybrid energy systems for sustainable energy solution - Laveet Kumar (11460088) (2024)
The present research investigates the techno-economic viability of two cases of hybrid energy systems for sustainable energy solutions in an urban area known for its abundant sunlight. These cases involve combinations of photovoltaic (PV) and biomass, with additional components such as an electrolyzer and fuel cell (FC). Case 1 comprises PV/biomass/electrolyzer, while Case 2 includes PV/biomass/fuel cell/electrolyzer/battery, aiming to produce electricity and hydrogen. This paper analyzed industrial power demands across off-season, middle-season, and peak-season periods. The optimal system for case 2 is the most reliable one with a 23645-kW PV panel, a 3800-kW biogas generator, a 3821-kW converter, a 250-kW fuel cell, a 600-kW electrolyzer, a 600-kg hydrogen storage tank (Htank), and a 30-battery backup system with a CC send-off strategy for off-season consumers. For peak-season users, the system has 23789-kW of PV panels, 3800-kW of biogas generators, 3861-kW of converters, 250-kW of FC, 1000-kW of electrolyzer, 1000-kg of Htank, and 30 battery backup room banks with an LF dispatch plan. The research findings suggest that utilizing PV/biomass/FC/electrolyzer/battery is a more feasible and economical strategy due to system benefits. The estimated increase in the LCOE was caused by the rising discount rate and fuel prices. Other Information Published in: International Journal of Hydrogen Energy License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.ijhydene.2024.05.369